Value of map sharing between multiple vehicles in the same field while using automated section control - Bennett, Jeffrey D. (Kansas State University, 2016)
Large acreage farms and even moderate sized farms employing custom applicators and harvesters have multiple machines in the same field at the same time conducting the same field operation. As a method to control input costs and minimize application overlap, these machines have been equipped with automatic section control (ASC). For nearly all these multiple-vehicle operations, over application is a concern especially for more irregularly shaped fields; however modern technology including automated guidance combined with automatic section control allow reduced doubling of input application including seeds, fertilizer, and spray. Automatic section control depends on coverage maps stored locally on each vehicle to determine whether or not to apply input products and up to now, there has not been a clear method to share these maps between vehicles in the same field. Without sharing coverage maps, an individual ASC planting unit only has location data where it has applied individually and no location data for where other planting units have applied seed in that same field. Automatic section control relies upon shared coverage maps to be continually updated between each planting unit and utilizes existing machine telematics infrastructure for map data sharing. Telematics utilizes a cloud computing platform and cellular connectivity which in rural areas is known to have limited service levels. Planting operations were simulated for two 16-row planters, each using two John Deere GreenStar3 2630 monitors, simulated GPS location data stream, electronic rate control units, and individual row unit clutches to have control at the finest granularity. Each simulated planting unit is equipped with automatic section control and telematics gateways to share coverage map data from the first planting unit to JDLink cloud infrastructure then out to the second. This study evaluates the impact that field size and shape have on using multiple ASC planters and coverage map sharing, and estimates seed cost savings from reducing over application because coverage maps are shared between planting units. The impact of sharing coverage maps with both planting units using field boundaries with automatic section control and without using field boundaries were evaluated. Guidance line headings were determined using AgLeader SMS’s mission planning feature to minimize the number of passes across each field based on the field boundary and implement width. Each field was run twice using parallel tracking, once each with and without coverage map sharing to observe the extent of over application. The field level data were then taken to examine a fictious 3,000 acre farming operation where the field level data was used as a partial composition of the farm operation. An embedded Microsoft Excel macro was used to create 8,008 different composition scenarios to determine farm level savings. The average farm savings was $58,909 per year. Additionally, using the 8,008 scenarios, time value of money was examined to determine the the minimum area required annually for five years for this technology to pay back. The average was 133 acres each year for five years. Equipment manufacturers and farmers have interest in these results. In general, equipment manufacturers desire to create a service-based product to be sold such that continual revenue path provides value added services after the precision agriculture hardware is sold. In this study, the existing telematics product offerings are tied to shared coverage maps to provide a value-add to an existing service. Farmers want to ensure this is a sound equipment investment with payback in a relatively short time period. As farm input costs continue to rise especially relative to crop prices, reducing over application will be critical to limit waste.
Keywords: Automated Section Control; Precision; Wireless Connectivity; Coverage Map Sharing